O homo viator no espaço da natureza : uma análise do Prólogo dos Milagros de Nuestra Señora, de Gonzalo de Berceo - Cunha, Viviane (2016)
Este breve estudio indaga en el Prólogo de los Milagros de Nuestra Señora de Gonzalo de Berceo en vinculación con el topos del hortus deliciarum. Tal espacio es el de la Naturaleza virgen, símbolo de María, teniendo en cuenta el desarrollo del culto mariano y observando el "crecimiento" de la figura de la Madre de Dios, desde la Antigüedad hasta los siglos XII y XIII
This brief study inquires into the Prologue of Gonzalo de Berceo's Milagros de Nuestra Señora, in connection it with the of the hortus deliciarum topos. Its space is that of the virgin Nature, a symbol of Mary, taking into account the development of Marian worship and the "growth" of the image of the Mother of God, from Antiquity to the 12th and 13th centuries
Keywords: Milagros de Nuestra Señora; Hortus deliciarum; Homo viator; Naturaleza; Culto mariano; Milagros de Nuestra Señora; Hortus deliciarum; Homo viator; Nature; Marian cult; Literatura religiosa; Hortus deliciarum; Milagros de Nuestra Señora; Becerro, Gonzalo de